A patient with penicillin-resistant viridans group streptococcal endocarditis and unusual reactions to vancomycin - Nopporn Apiwattanakul (2018)
There is a paucity of data regarding the treatment of endocarditis caused by penicillin-resistant viridans group streptococci (PR-VGS). We report a 16-year-old girl who had native-valve endocarditis due to PR-VGS which was identified as Streptococcus mitis. She also had unusual reactions to vancomycin. Eighteen hours after initiation of 50 mg/kg/day vancomycin, she developed a maculopapular rash, then at 48 hours she developed an intermittent high fever and a progressive decrease in peripheral leukocytes and platelets. She developed hypotension on Day 8. Her serum C-reactive protein and procalcitonin levels were high. All reactions improved after vancomycin was discontinued and oral prednisolone was started. This unusual combination of reactions to vancomycin was likely caused by immune and nonimmune mechanisms. Her endocarditis was successfully treated with cefotaxime 200 mg/kg/day for 4 weeks.